A review of Psoralea corylifolia L.: a valuable plant with profound biological significance - Yang, Anni; Kong, Lingping; You, Zhibo; Li, Xinyu; Guan, Jian; Li, Fengjin; Zhong, Lingyun; Jiang, Hai (Frontiers in Pharmacology, 2025)
Psoralea corylifolia L. (PCL) is an annual herb of the genus Psoralea in the family Fabaceae, and its mature fruit can be used medicinally as a precious medicinal herb to tonify muscles and bones. With the deepening of research, its applications to various industries, including food, agriculture, and cosmetics, with products being developed in countries such as Vietnam, India, and Japan. A total of 321 metabolites, including coumarins, flavonoids, meroterpenes, benzofurans, and dimers, were identified in PCL. PCL and related products have demonstrated therapeutic effects, such as antiosteoporosis effects, estrogen-like effects, anti-inflammatory properties, neuroprotection, antitumor activity, and vitiligo treatment. The expression mechanisms of these pharmacological effects are closely related to the regulation of the immune system, the inhibition of oxidative stress, and the induction of apoptosis. This paper summarizes the latest research on the ethnobotany, phytochemistry, processing technology, pharmacology, and hepatotoxicity of PCL. Furthermore, bibliometric analysis was used to systematically analyze the research hotspots and trends in PCL, which have never been addressed in previous reviews of PCL. In the future, it will be necessary to focus on the active metabolites of PCL, analyze its targets and signaling pathway network to address potential toxicity and side effects in clinical applications, and further expand the potential application of PCL in medicine.